Predictors of Neurosurgical Outcomes in Traumatic Brain Injury: A Study from Banda Aceh, Indonesia - Niazie, Azzie; Jasa, Zafrullah Khany; Rahmi, Rahmi; Yusmalinda, Yusmalinda (Jurnal Neuroanestesi Indonesia, 2026)
Introduction: Traumatic brain injury (TBI) remains a major global health challenge and frequently requires neurosurgical intervention. Various clinical, surgical, and systemic factors may influence postoperative morbidity and mortality. This study aimed to identify key predictors of postoperative outcomes in patients with TBI undergoing neurosurgical procedures.Subject and Method: A prospective cohort study was conducted at Dr. Zainoel Abidin General Hospital in Banda Aceh from July to October 2024, involving 48 TBI patients who were selected through total sampling. Statistical analysis using chi-square tests and multiple logistic regression identified significant predictors.Results: We enrolled 48 patients, with an overall postoperative morbidity rate at 58.3%, and the mortality rate was 22.9%. Morbidity was significantly associated with preoperative GCS score (p=0.001), injury-to-surgery time (p=0.039), respiratory (p=0.007), and cardiovascular system (p=0.001). Mortality was significantly associated with preoperative GCS score (p=0.002), surgery duration (p=0.041), respiratory (p=0.041), and cardiovascular system (p=0.004). Multivariate analysis confirmed the preoperative GCS score was the most significant predictor of both morbidity and mortality (p0.05).Conclusion: A low preoperative GCS score is a strong predictor of poor postoperative outcomes in patients with TBI. Optimizing perioperative management may improve clinical outcomes in TBI patients undergoing neurosurgical intervention